Malawi's Progress Toward Shared Prosperity Since 2004 - World Bank (World Bank, Washington, DC, 2019)
Due to recurring shocks and resulting weak economic growth, Malawi has not experienced meaningful poverty reduction since 2004. In fact, poverty has been on the raise in rural areas. As poverty is mainly a rural phenomenon in Malawi and most of the poor engage in crop production, this report briefly explores agricultural practice of the poor farmers. Since 2010, consumption of households at the bottom of the welfare distribution has increased significantly. This has reduced inequality and ultra-poverty. Decomposition of poverty changes indicates that favorable redistribution has contributed to poverty reduction after 2010, but lack of growth hinders progress in poverty reduction. Despite seemingly unchanging poverty since 2004, there is enormous seasonality in well-being, and poverty is much higher during lean season. Analysis of poverty and consumption across quarters of a given agricultural year (from harvest to lean season) shows that poverty is relatively low in the harvest season, but it increases continuously and reaches its peak in the lean season. This seasonal variation in well-being is pronounced in drought years.The farm input subsidy program (FISP), one of the key agriculture policy interventions implemented by the government of Malawi, has increased applications of fertilizer in the country relative to neighboring countries or the Sub-Saharan Africa average. Even if the FISP has increased fertilizer application rate relative to neighboring countries, agriculture technology adoption is lower among poor farmers and is on the decline since 2010. As a result, crop yield is lower for poor farmers.